FUNGSI DAN DAMPAK MITOS “EYANG SAPU JAGAD” BAGI KEHIDUPAN MASYARAKAT DUSUN UBALAN DAN DESA MAGUAN KABUPATEN MALANG - Widi Sukmawati Trisnatul Rohma; Eggy Fajar Andalas (Universitas 17 Agustus 1945 Surabaya, 2022)
The myth of “Eyang Sapu Jagad” is an oral literature that lives in the people of Ubalan Hamlet and Maguan Village, Malang Regency, East Java. This myth is important for the people of the two regions because it is considered to have an influence on the social life of the community to this day. This study aims to describe the function and impact of myths on the lives of the people of the two regions. The research uses a descriptive-qualitative design with a sociology of literature approach. The data sources are informants from both regions, observation, notes, and documentation. Data were collected using recording, observation, documentation, interviewing and recording techniques. The results showed that the myth of “Eyang Sapu Jagad” had a strong influence on people's lives. For the people of Uba-lan Hamlet, myths function as a means of strengthening a sense of solidarity between community members, social control for community life, and promoting tourism, so that they have an impact on their social and spiritual life which is reflected in the act of imposing a container, ritual traditions of prayer, ethics live in society, and cultivate the community's economy. For the people of Maguan Village, myth serves as a means of strengthening a sense of solidarity among community members and a medium for education, so that it has an impact on their social and spiritual life which is represented through collective action to carry out petilasan, ritual traditions of prayer, yasinan and slametan on Friday Legi, as well as being guideline in community life.